A Spatial Econometric Approach on Addressing Determinants of Regional Inequality - Rizal Syaifudin; Togi Haidat Mangara; Deris Desmawan; Sugeng Setyadi (Universitas Negeri Semarang, 2025)
The disparity in socioeconomic conditions across Banten Province is suspected to contribute to regional inequality, stemming from uneven economic development. This is evidenced by certain areas with significantly higher economic levels than others. This study uses correlational and spatial approaches to analyze the influence of these socioeconomic conditions on the high level of regional inequality in Banten Province. The socioeconomic variables examined include the Human Development Index (HDI), labor force participation rate, poverty rate, base economic sector, and economic growth. The findings indicate that the poverty rate significantly correlates with regional inequality in a non-spatial context. Meanwhile, the base economic sector (particularly manufacturing) and economic growth show significant spatial effects on regional inequality.